How do you do this equation if someone can please explain this step by step
2x+5 -x-4 =1
x+4 x-5
The common denominator is (x+4)(x-5), so multiplying both sides by this gives:
$\displaystyle (x+4)(x-5)\left[\frac{2x+5}{x+4}-\frac{x-4}{x-5}\right]=1(x+4)(x-5)$
$\displaystyle (2x+5)(x-5)-(x-4)(x+4)=(x+4)(x-5)$
$\displaystyle 2x^2-5x-25-x^2+16=x^2-x-20$
Oh, this is easier than I previously thought...The squared terms dissapear...
$\displaystyle -5x-9=-x-20$
$\displaystyle 4x=11$
$\displaystyle x=\frac{11}{4}$